2020
DOI: 10.1007/s00248-020-01544-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in Physicochemical Profiles and Bacterial Communities Associated with Aedes aegypti Breeding Sites and Larvae on Guadeloupe and French Guiana

Abstract: Aedes aegypti develop in aquatic habitats in which mosquito larvae are exposed to physicochemical elements and microorganisms that may influence their life cycle and their ability to transmit arboviruses. Little is known about the natural bacterial communities associated with A. aegypti or their relation to the biotic and abiotic characteristics of their aquatic habitats. We characterized the physicochemical properties and bacterial microbiota of A. aegypti breeding sites and larvae on Guadeloupe and in French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 77 publications
3
39
0
3
Order By: Relevance
“…While Herbiconiux was previously identified in Ae. aegypti larvae (Hery et al, 2021), and it is present also in our wild sampled larvae, Leifsonia was found in Ae. albopictus for the first time.…”
Section: Developmental Stage Affects Microbiota Compositionsupporting
confidence: 65%
See 1 more Smart Citation
“…While Herbiconiux was previously identified in Ae. aegypti larvae (Hery et al, 2021), and it is present also in our wild sampled larvae, Leifsonia was found in Ae. albopictus for the first time.…”
Section: Developmental Stage Affects Microbiota Compositionsupporting
confidence: 65%
“…Additionally, specific physical and chemical parameters (i.e., oxygen and conductivity) were found to be associated with microbiota composition in Ae. aegypti (Hery et al, 2021). Thus, in an attempt to provide a qualitative analysis that could support the metagenomic results, a set of physical and chemical parameters were measured for both W Start and W End samples.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in different environments showed a fuzzy association between physicochemical characteristics of larval habitats and container types. However, differences in some parameters such as total dissolved solids, water hardness, electrical conductivity, chemical oxygen demand and conductivity could be linked to container nature (i.e., natural or artificial) and water origin (Chatterjee et al, 2015;Gnanasoundari et al, 2017;Hery et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since resource depletion can mediate the regulatory effects of larval competition on the temperature-dependence of rm, it is also important to determine the temperature-dependence of resource availability itself (Huey and Kingsolver 2019). For example, recent studies show that mosquitoes can be reared exclusively on cultures of Asaia bacteria (Chouaia et al 2012, Souza et al 2019, that microbiota at mosquito breeding sites is spatially heterogenous (Hery et al 2021), and that larval exposure to microbial variability can affect adult mosquito life history traits (Dickson et al 2017). Microbial growth rates also increase with temperature to some optimum, so the concentration of food in the environment may also increase (Craine et al 2010, Cross et al 2015, Smith et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, shifts in environmental temperature could alter the concentration of food in the environment, which could affect the growth of detritivore populations. While recent studies have provided useful insights into the relationships between microbes, detritus and mosquito vectors (Yee et al 2007;Chouaia et al 2012;Dickson et al 2017;Souza et al 2019;Hery et al 2021), future work could focus on the temperature-dependencies of these relationships.…”
Section: Discussionmentioning
confidence: 99%